PENGUATAN SIKAP TOLERANSI DAN PERDAMAIAN DALAM KEHIDUPAN SOSIAL MELALUI SOSIALISASI PADA PAGUYUBAN ISTRI PEDULI (PIP) - Hasna Putri Hanifah; Wulida Itsnaini; Mutmainah Mutmainah; Dewi Asih Nusantari (STKIP Subang, 2026)
Indonesia's pluralistic society requires the reinforcement of tolerance and peace values, particularly at the community level. The Paguyuban Istri Peduli (PIP), a social organization in Mekarjaya Village, Gantar District, Indramayu Regency, whose members come from diverse backgrounds, faces challenges in internalizing these values. This community service activity aimed to enhance PIP members' understanding of tolerance, peace, and religious moderation, as well as to strengthen the role of wives in social life. The method employed was participatory socialization through material presentation, interactive discussions, and collective reflection. The activity was conducted on February 20, 2026, and was attended by 25 participants. The results showed active participant engagement in discussing everyday issues such as neighborly conflicts, differing perspectives within families, parent-child communication, and interfaith workplace ethics. Participants demonstrated an increased understanding of active tolerance, effective communication, and awareness of the strategic role of wives as agents of peace within their families and communities. This activity successfully encouraged critical reflection and a shift in perspective regarding how to address differences. It is concluded that participatory socialization is effective in strengthening tolerance and peace values and in affirming the role of wives in building sustainable social harmony.